2022
DOI: 10.1002/hon.2975
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric antigen receptor T‐cell therapy combined with autologous stem cell transplantation improved progression‐free survival of relapsed or refractory diffuse large B‐cell lymphoma patients: A single‐center, retrospective, cohort study

Abstract: Autologous hematopoietic stem cell transplantation (ASCT) and chimeric antigen receptor T-cell therapy (CART) are salvage therapies that are utilised for treatment of relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL).However, whether the combination therapy of ASCT and CART (ASCT-CART) can improve the survival of R/R DLBCL remains unknown. Overall, 67 R/R DLBCL patients were included, among which 21 patients underwent ASCT-CART therapy and 46 patients underwent ASCT therapy. The median number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…A recent study has demonstrated that auto-HSCT in combination with CAR-T cell therapy achieved higher ORR, PFS, and OS compared with CAR-T cell therapy alone, indicating that bridging auto-HSCT is able to promote durable and deep remission (115). Another clinical trial has compared the efficacy of the combination of auto-HSCT and CAR-T cell therapy with auto-HSCT alone, and it showed that the combination group had higher CR rate and 3-year PFS than the auto-HSCT group, with lower 3 year relapse rate (116). The above studies suggest that the combination of auto-HSCT and CAR-T cell therapy could exert a synergistic effect in remission induction (114,(116)(117)(118).…”
Section: Bridging Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has demonstrated that auto-HSCT in combination with CAR-T cell therapy achieved higher ORR, PFS, and OS compared with CAR-T cell therapy alone, indicating that bridging auto-HSCT is able to promote durable and deep remission (115). Another clinical trial has compared the efficacy of the combination of auto-HSCT and CAR-T cell therapy with auto-HSCT alone, and it showed that the combination group had higher CR rate and 3-year PFS than the auto-HSCT group, with lower 3 year relapse rate (116). The above studies suggest that the combination of auto-HSCT and CAR-T cell therapy could exert a synergistic effect in remission induction (114,(116)(117)(118).…”
Section: Bridging Therapiesmentioning
confidence: 99%
“…Another clinical trial has compared the efficacy of the combination of auto-HSCT and CAR-T cell therapy with auto-HSCT alone, and it showed that the combination group had higher CR rate and 3-year PFS than the auto-HSCT group, with lower 3 year relapse rate (116). The above studies suggest that the combination of auto-HSCT and CAR-T cell therapy could exert a synergistic effect in remission induction (114,(116)(117)(118). In addition, localized radiotherapy and cryoablation are effective bridging therapies for R/R MM patients with bulky mass.…”
Section: Bridging Therapiesmentioning
confidence: 99%
“…It has been reported in the literature that CRS was observed in 37% to 93% of patients with hematologic malignancies treated with autologous CD19-CAR T cells ( 6 8 ). Wang T analyzed the safety of 21 patients with DLBCL treated with ASCT-CART, and the results showed that 71% of patients developed grade 1-2 CRS and 5% of patients suffered from grade 3-4 CRS ( 9 ). The incidence and degree of CRS depend on tumor type, tumor burden, CAR-T cell dose, co-stimulatory domain type, CAR T cell activation, and expansion ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al compared CAR T cell infusion after ASCT and CAR T cells alone and demonstrated that the best ORR, CR rate and long-term outcomes improved significantly in the combination group (62). In another study comparing CAR T cell infusion after ASCT and ASCT alone, the combination group showed higher CR rate (71% vs. 33%; p=0.003) and 3year PFS (80% vs. 44%; p=0.036) than the ASCT group, and demonstrated lower 3 year relapse/progression rate (15% vs. 56%; p=0.015) (63). Incidences of adverse events differ from studies and were manageable in most cases (Table 2).…”
Section: Combination With Hsctmentioning
confidence: 96%